O ensino religioso na cidade de Apodi-RN: história, formação e perfil docente na rede municipal de ensino. - Silva, Maciel Rodrigues da (2019)
This dissertation, which is related to the line of research Brazilian Religious Field, aims to analyze the formation and the profile of Religious Education (RE) teacher in the city of Apodi, Rio Grande do Norte, in its pedagogical application as an area of knowledge and basic and citizen formation according to LDBEN No. 9394/1996 and its update in Law No. 9475/1997. The theoretical models of the RE applied by the teachers and their adaptations in the proposals of the State Education Network assumed by the Apodi Education Secretariat will be considered in the investigation. The course of the methodology was adopted through qualitative analysis, involving the theoretical and historical research of Religious Education in the Brazilian socio-political context and in the regional context of Rio Grande do Norte, especially in the lands of Apodi. Then, a survey was conducted with the RE teachers, all from the municipal education system, through a semi-structured interview to know their profile and their conceptions about training and teaching in this area. Finally, based on the literature of the Sciences of Religion, questions and pedagogical suggestions were raised in order to assure the students of public schools access to religious knowledge produced by humanity, contributing to the respect for the cultural diversity of the county.